Low C3 Serum Levels Predict Severe Forms of STEC-HUS With Neurologic Involvement - Netti, Giuseppe Stefano; Santangelo, Luisa; Paulucci, Leonardo; Piscopo, Giovanni; Torres, Diletta D.; Carbone, Vincenza; Giordano, Paolo; Spadaccino, Federica; Castellano, Giuseppe; Stallone, Giovanni; Gesualdo, Loreto; Chironna, Maria; et al. (Frontiers in Medicine, 2020)
Background: The correlation between the severity of hemolytic uremic syndrome related to Shiga toxin–producing Escherichia coli (STEC-HUS) and involvement of the complement system has been examined in a small number of studies, with conflicting results. In the present study we investigated whether serum C3 levels on admission are associated with neurologic involvement. Methods: To this purpose, 68 consecutive STEC-HUS patients were recruited and main clinical and laboratory variables ad hospital admission were compared between those with or without neurologic involvement. Results: STEC-HUS patients who developed neurologic involvement (NI) showed significant higher leukocyte count, c-reactive protein, and hemoglobin, and lower sodium levels as compared with those without. Interestingly, baseline serum levels of C3 were significantly lower in patients with NI as compared with those without (p<0.001). Moreover, when stratified according to need of Eculizumab rescue therapy due to severe NI, patients treated with this drug showed baseline C3 serum levels significantly lower than those who were not (p<0.001). Low C3 was independent risk factor for NI in our patients’ population when entered as covariate in a multivariate logistic regression analysis including other major variables previously proposed as possible predictors of poor prognosis in STEC-HUS (for instance, leukocyte count, c-reactive protein, sodium levels) (HR 6.401, 95%CI 1.617-25.334, p=0.008 for C3). To underline the role of Complement in the worsening of STEC-HUS patients’ clinical conditions and outcomes, all patients were divided into two groups according to the baseline lower vs normal serum levels of C3 and the main data on care needs were assessed. Interestingly more patients with lower C3 serum levels required renal replacement therapy (p=0.024), anti-hypertensive therapy (p=0.011), Intensive Care Unit admission (p=0.009) and longer hospitalization (p=0.003), thus displaying significantly more severe disease features as compared with those with normal C3 serum levels. Conclusions: Our data suggests that children with STEC-HUS with decreased C3 concentrations at admission are more likely to develop neurologic involvement and are at increased risk of having serious clinical complications.